Maternal-derived galectin-1 shapes the placenta niche through Sda terminal glycosylation: implication for preeclampsia - Xie,Y; Zhao,F; Freitag,N; Borowski,S; Wang,Y; Harms,C; Pang,P-C; Desforges,J; Wen,T; Schwedhelm,E; Singh,M; Dechend,R; et al. (PNAS Nexus, 2023)
Placental abnormalities cause impaired fetal growth and poor pregnancy outcome (e.g. preeclampsia [PE]) with long-lasting consequences for the mother and offspring. The molecular dialogue between the maternal niche and the developing placenta is critical for the function of this organ. Galectin-1 (gal-1), a highly expressed glycan-binding protein at the maternal–fetal interface, orchestrates the maternal adaptation to pregnancy and placenta development. Down-regulation or deficiency of gal-1 during pregnancy is associated with the development of PE; however, the maternal- and placental-derived gal-1 contributions to the disease onset are largely unknown. We demonstrate that lack of gal-1 imposes a risk for PE development in a niche-specific manner, and this is accompanied by a placental dysfunction highly influenced by the absence of maternal-derived gal-1. Notably, differential placental glycosylation through the Sda-capped N-glycans dominates the invasive trophoblast capacity triggered by maternal-derived gal-1. Our findings show that gal-1 derived from the maternal niche is essential for healthy placenta development and indicate that impairment of the gal-1 signaling pathway within the maternal niche could be a molecular cause for maternal cardiovascular maladaptation during pregnancy.